Donor–Acceptor Copolymers with Rationally Regulated Side Chain Orientation for Polymer Solar Cells Processed by Non-Halogenated Solvent - Hu, Zhengwei; Huang, Qiri; Liu, Chunchen; Song, Ao; Shao, Lin; Bai, Yuanqing; Hu, Zhicheng; Zhang, Kai; Huang, Fei; Cao, Yong (Organic Materials, 2022)
A donor–acceptor (D-A) conjugated polymer PBTFO-T-1 consisting of 2,1,3-benzothiadiazole (BT) as A unit and thiophene (T) as D unit was facilely obtained by a straightforward three-step reaction. The BT unit is attached with a fluorine atom and an alkoxy chain to simultaneously endow the polymer with a deep HOMO energy level and desirable solubility. The alkoxyl chain orientation on the BT unit has been regulated and the polymer PBTFO-T-2 with regio-regularly oriented side chains was also developed to investigate the impact of the alkoxyl chain orientation on their optoelectronic properties. The PBTFO-T-1:Y6-BO polymer solar cells (PSCs) were processed with a non-halogenated solvent and achieved an optimized power conversion efficiency of 14.16%, significantly higher than 9.39% of the PBTFO-T-2:Y6-BO counterpart. It has been demonstrated that the PBTFO-T-1:Y6-BO film exhibits higher and more balanced charge transportation and superior film morphology, resulting in higher exciton generation and dissociation, less recombination and eventually the higher short-circuit current density (Jsc) and fill factor. This study provides a possible strategy to develop polymer donors with low cost for future commercial applications of PSCs and gives some insights into regulating optoelectronic properties of polymer donors via rationally modifying their side chain orientation.
Keywords: polymer donor; non-halogenated solvent; regio-regular orientation